PROFITABILITAS DAN FAKTOR-FAKTOR LAINNYA YANG MEMPENGARUHI NILAI PERUSAHAAN - ARIES JONATHAN; IRMADELLA MARSIL (E-Jurnal Akuntansi TSM, 2021)
The purpose of this research is to obtain empirical evidence regarding the effect of profitability, dividend policy, institutional ownership, firm size, total asset turnover, managerial ownership, investment decisions, and liquidity on firm value.This research was conducted on all non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2019. The sampling method in this research used a purposive sampling method, so it requires criteria in taking the sample to be examined. In the end, this research will examine 70 companies that passed the criteria with a total of 210 data. Hypothesis testing conducted in this research using multiple linear regression. The results of the research showed that profitability, institutional ownership and investment decisions had an effect on firm value. On the other hand, dividend policy, firm size, total asset turnover, managerial ownership, and liquidity had no effect on firm value.